LEARNING DEVICE REQUIREMENT SCIENCE EDUCATION BY PROBLEM BASED LEARNING (PBL) TO INCREASE HIGH ORDER THINKING SKILLS JUNIOR HIGH SCHOOLS - Fuaidah, Nur; Madlazim, Madlazim; Agustini, Rudiana (JPPS (Jurnal Penelitian Pendidikan Sains), 2020)
At this 21st century, thinking ability for students based on High Order Thinking Skills. This research was to analyze learning device requirement science education by Problem Based Learning to increase High Order Thinking Skills junior high school. This research method is using 4D model. Learning tools developed consist of syllabus, lesson plans, work sheet, and assessment sheets. The device was tested in class IX with a total of 20 students in one of the junior high schools Pasuruan. Data collection using the method of validation, observation, tests, and questionnaires. Data analysis techniques using quantitative descriptive methods. The findings of the research are: (1) the validity of the learning kit with an average syllabus component, lesson plans, worksheet, and assessment sheet obtaining a very valid category so that it can be used in teaching and learning. (2) the practicality of learning tools is obtained from the implementation of lesson plans from two observers with very good categories so that it can be concluded practically in learning activities and the obstacles encountered during learning activities can be overcome without the learning process experiencing significant disturbances. (3) effectiveness is indicated by the increase in HOTS characterized by n-gain results were 19 students as high and 1 student as moderate, while the students' responses to the learning component are happy, interesting and makes learning material easy to understand. Based on data analysis, it can be concluded that the natural science learning material based on PBL model is feasible to increase HOTS.